Clot Component Reacting with Thrombin - Kowarzyk, Hugon; Głogowska, Irena; Szymik, Stanisław (Thrombosis and Haemostasis, 1962)
The fibrin clot induced by a minimum amount of thrombin contains two components: one which forms the fibrin polymer spontaneously and another which does not form the polymer except in the presence of thrombin. The latter component produces non-protein nitrogen like fibrinogen itself, when reacting with thrombin. It is reasonable to conclude that the fissile component of the clot is an intermediate product of the fibrin formation.